2020
DOI: 10.2174/1570159x17666191101124017
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Neuronal Activity of Prefrontal Cortex: New Directions for the Therapy of Depression

Abstract: Depression is one of the prevalent psychiatric illnesses with a comprehensive performance such as low self-esteem, lack of motivation, anhedonia, poor appetite, low energy, and uncomfortableness without a specific cause. So far, the cause of depression is not very clear, but it is certain that many aspects of biological psychological and social environment are involved in the pathogenesis of depression. Recently, the prefrontal cortex (PFC) has been indicated to be a pivotal brain region in the pathogenesis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 147 publications
(182 reference statements)
0
5
0
Order By: Relevance
“…The functional, structural, and system-level abnormalities of PFC have been reported in both preclinical and clinical studies (Wang et al, 2021 ; Pizzagalli and Roberts, 2022 ). Various treatment interventions, including ketamine, have been observed to mechanically rescue PFC dysregulation (Zhou et al, 2020 ; Ma et al, 2022 ). In addition, regulation of the PFC-hippocampus circuit has been shown to be associated with the rapid onset of ketamine’s antidepressant effect (Carreno et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The functional, structural, and system-level abnormalities of PFC have been reported in both preclinical and clinical studies (Wang et al, 2021 ; Pizzagalli and Roberts, 2022 ). Various treatment interventions, including ketamine, have been observed to mechanically rescue PFC dysregulation (Zhou et al, 2020 ; Ma et al, 2022 ). In addition, regulation of the PFC-hippocampus circuit has been shown to be associated with the rapid onset of ketamine’s antidepressant effect (Carreno et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, long-term abnormalities or imbalances in prefrontal activity have been suggested as a pathophysiological mechanism for psychiatric disorders, since chronic stress exposure could lead to anxiety disorder and depression (Zhou et al, 2019). DREADDs subserve to mimic or reverse such long-term circuitry changes that are beyond the reach of conventional acute blockade and/or irreversible lesioning.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been demonstrated that acute and chronic silencing of PFC interneurons had opposite impacts on anxiety-like behavior in mice ( Soumier and Sibille, 2014 ), suggesting that short- versus long-term manipulations of local circuits may differentially alter PFC network functions. In addition, long-term abnormalities or imbalances in prefrontal activity have been suggested as a pathophysiological mechanism for psychiatric disorders, since chronic stress exposure could lead to anxiety disorder and depression ( Zhou et al, 2020 ). DREADDs subserve to mimic or reverse such long-term circuitry changes that are beyond the reach of conventional acute blockade and/or irreversible lesioning.…”
Section: Discussionmentioning
confidence: 99%
“…The LBRD standard decoction imparted a protective effect against the reduction of neuron expression induced by chronic stress. Numerous evidences demonstrate that a decrease in the number of neurons in the prefrontal region reflects the pathology of depression, and it is encouraging to note that treatment with the LBRD standard decoction reversed ablation of neurons [ 63 65 ].…”
Section: Discussionmentioning
confidence: 99%